A new diffusion and substitution based cryptosystem for securing medical image applications. (2018) - Mancy, L.; Vigila, S. Maria Celestin
Due to the rising privilege for tele-health facilities have sophisticated responsiveness in the usage of medicinal image safeguard proficiency. It mainly compact with patient records that are secretive and must only available to legal person. So the medical image safety becomes a very significant problem, when patient evidence is conveyed through the public network. In this paper, a secret key of 128-bits size is generated by an image histogram. Initially, the photo sensitive feature of digital imaging and communications in medicine image is decomposed by the mixing process. The resulting image is distributed in key reliant blocks and further, these blocks are passed through key reliant diffusion and substitution processes. A total of five rounds are used in the encryption method. Finally the generated secret key is embedded within the encrypted image in the process of steganography. This also enhances the security of proposed cipher. At the receiver side the secret key was recovered from the embedded image and decryption operation was performed in inverse format. Performance analysis designates that the proposed cipher is more secure.